THE STUDY OF MISHKĀT AL-MAṢĀBĪḤ BY ABU ABDILLAH AL-TIBRIZI: As a Secondary Book of Hadith in Medieval Era - Hanif, Naufal Aulia; Husnia, Nisrina Aidaturahma (Nabawi: Journal of Hadith Studies, 2023)
This article attempts to describe the characteristics of one of the hadith books that appeared in the Middle Ages by introducing one of the hadith books that were successfully compiled. Namely, the book Mishkāt al-Maṣābīh by Abu Abdillah al-Tibrizi. Even though it is a secondary hadith book which is rarely studied and researched in the current era, the role of the data in the the book is very important to be elaborated with historical data that the authors found to describe the trend of the development of hadith in the Middle Ages. In this qualitative research, the author used a descriptive-analytical method with a literature study model to look for the characteristics and features of Misykāt al-Maṣābīh}in the development of hadith studies. For this reason, this article raises several important issues regarding the object discussed. First, a general discussion about the development of medieval hadith to describe the position of this book in the midst of the social conditions of society at that time. Second, a discussion of the biography and intellectual journey of Abu Abdillah al-Tibrizi. Third, a special discussion of the method and systematics of compiling the book and its advantages and disadvantages. The author finds that Abu Abdillah al-Tibrizi contributed to the development of hadith by providing additional information about the names of narrators and cutting narrators only at the companion level, in addition to introducing three categorizations in composing hadith as an innovation that emerged. [Artikel ini berusaha memaparkan karakteristik dari salah satu kitab hadis yang muncul pada abad pertengahan dengan mengenalkan salah satu kitab hadis yang berhasil disusun, yaitu kitab Misykāt al-Maṣābīh} karya Abu Abdillah al-Tibrizi. Walaupun termasuk kitab hadis sekunder yang jarang dikaji dan diteliti di era sekarang, peran data-data dalam kitab tersebut sangat penting dielaborasikan dengan data historis yang penulis temukan. Untuk menggambarkan tren perkembangan hadis pada abad pertengahan. Dalam penelitian kualitatif ini, penulis menggunakan metode deskriptif-analitis dengan model kajian kepustakaan untuk mencari karakteristik dan keistimewaan kitab Misykāt al-Maṣābīh} dalam perkembangan kajian hadis. Untuk itu, artikel ini mengangkat beberapa persoalan penting mengenai objek yang dibahas. Pertama, pembahasan secara umum seputar perkembangan hadis abad pertengahan untuk menggambarkan posisi kitab ini di tengah kondisi sosial masyarakat ketika itu. Kedua, pembahasan mengenai biografi dan perjalanan intelektual Abu Abdillah al-Tibrizi. Ketiga, pembahasan khusus mengenai metode dan sistematika penyusunan kitab serta kelebihan dan kekurangannya. Penulis menemukan bahwa Abu Abdillah al-Tibrizi turut berkontribusi dalam perkembangan hadis dengan memberikan tambahan info mengenai nama perawi dan memotong rawi hanya pada tingkat sahabat saja selain mengenalkan tiga kategorisasi dalam menyusun hadis sebagai sebuah inovasi yang dimunculkan).]